1978
DOI: 10.1007/bf00611908
|View full text |Cite
|
Sign up to set email alerts
|

Determination of microsomal UDP-glucuronyltransferase in needle-biopsy specimens of human liver

Abstract: Sensitive, reliable and convenient assays are described for the study of human liver microsomal UDP-glucuronyltransferase. Using 14C-1-naphthol as substrate about 2 mg of a liver biopsy specimen and for 14C-morphine about 20 mg of tissue will suffice for enzyme estimation. Lack of inhibition of 1-naphthol glucuronidation by morphine suggests that the substrates are glucuronidated by different forms of the enzyme. Enzyme levels in the native and activated state were studied in biopsies from patients grouped acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…Such substrates can be used as specific inhibitors to identify the UGT isoform(s) contributing to the glucuronidation of drugs (Court, 2005). However, previous reports have shown confusing results, namely that 4-nitrophenol and 1-naphthol, typical substrates for human UGT1A6, inhibited UGT1A1, UGT1A4, or UGT2B7-catalyzed glucuronidations in human liver microsomes but did not inhibit the activities by recombinant UGTs (Bock et al, 1978;Dahl-Puustinen and Bertilsson, 1987;Rajaonarison et al, 1991;Hanioka et al, 2001b). In the present study, we found that 1-naphthol showed more potent inhibition of the UGT1A1-and UGT1A4-catalyzing activities in human liver microsomes than that by recombinant enzymes (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such substrates can be used as specific inhibitors to identify the UGT isoform(s) contributing to the glucuronidation of drugs (Court, 2005). However, previous reports have shown confusing results, namely that 4-nitrophenol and 1-naphthol, typical substrates for human UGT1A6, inhibited UGT1A1, UGT1A4, or UGT2B7-catalyzed glucuronidations in human liver microsomes but did not inhibit the activities by recombinant UGTs (Bock et al, 1978;Dahl-Puustinen and Bertilsson, 1987;Rajaonarison et al, 1991;Hanioka et al, 2001b). In the present study, we found that 1-naphthol showed more potent inhibition of the UGT1A1-and UGT1A4-catalyzing activities in human liver microsomes than that by recombinant enzymes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4-Nitrophenol inhibited UGT2B7-catalyzed 3Ј-azido-3Ј-deoxythymidine glucuronidation (Rajaonarison et al, 1991) and UGT1A4-catalyzed amitriptyline glucuronidation (Dahl-Puustinen and Bertilsson, 1987) in human liver microsomes. 1-Naphthol inhibited UGT2B7-catalyzed morphine glucuronidation (Bock et al, 1978) and UGT1A1-catalyzed SN-38 glucuronidation (Hanioka et al, 2001b) in human liver microsomes. It should be noted that the inhibition of SN-38 glucuronidation by 1-naphthol was not observed when recombinant UGT1A1 was used as an enzyme source (Hanioka et al, 2001b discrepancies between the inhibitory effects of such compounds on glucuronidation in human liver microsomes and those by recombinant UGTs.…”
mentioning
confidence: 99%
“…The enzyme product was sep-arated from the unreacted substrate as described for UDP-glucuronyl transferase towards 1-naphthol by Bock et al [ 1978]. Standard incubation mixture (final volume 50 pi) contained 0.25 mol/l sodium pyrophos phate buffer (pH 5.5).…”
Section: Assaysmentioning
confidence: 99%
“…Morphine is subject to marked presystemic elimination (Brunk & Delle, 1974;Sawe et al, 1981) predominantly by glucuronidation in the liver and the gut mucosa (Iwamoto & Klaassen, 1977;Bock et al, 1978). In the clinical use of oral morphine this is compensated for by administration of higher oral than parenteral doses.…”
Section: Introductionmentioning
confidence: 99%